Nivel de conocimientos y actitudes hacia métodos anticonceptivos en estudiantes de ciencias de la salud de la Universidad Nacional de la Amazonía Peruana, Iquitos, 2013 - Loayza Boullosa, Elizabeth Cristina (2013)
In many countries,women and couples mainly depend on one or two kind of contraceptive methods, this happens because of the govemment politics and it has as consequences the ignorance about another sort of methods which they can use to decrease the young pregnancy rate, accidentally or without any planning about it. Because of this social problem, the main objective for this investigation was precisely to find the connection between the knowledge with the attitudes towards the contraceptive methods which could fluctuate between adequate or inadequate and negative or positive attitude according to the truthful results. The established hypothesis here was "There is a connection between the knowledge with the attitudes towards the contraceptive methods in health sciences students from The National University ofthe Peruvian Amazon, 2013". The method used for this research was the quantitative non experimental of a descriptive correlational of transverse cross, being the samples taken from 115 students of health sciences from The National University of the Peruvian Amazon - 2013 using the samples in conformity of the same population applying two instruments of evaluation, an objective test of knowledge with a content validity of 89, 9% a reliability of 77,1 %. And a scale of attitude type Likert with a content validity of95,7% anda reliability of 86,7%. To the analysis and the interpretation of these results were used a SPSS statistical packet version 18 and the continuance correction statistical of Yates, to the results of the samples they got a significant ofp = 0.197 >a= 0.05which indicates that the hypothesis ofthis research was rejected. What means that it does not exist statistically significant connection between the knowledge with the attitudes towards the contraceptive methods in the students. So that it was not allowed to accept the hypothesis but we could have a very important finding in this investigation